Application of Raman spectroscopy to diagnose the metabolic state of volleyball and soccer players through the identification of urine components. Issue 4 (3rd July 2020) - Bernal-Reyes, Fernando; Acosta-Elias, Mónica; Burgara-Estrella, Alexel J.; Álvarez-Bajo, Osiris; Gavotto-Nogales, Omar I.; Antunez-Dominguez, Francisco J.; Placencia-Camacho, Lucia; Sarabia-Sainz, Héctor M.
Abstract: Raman spectroscopy is a rapid technique that allows the simultaneous determination of several components of urine to assess the metabolic status. In this study, the urine composition was evaluated in volleyball and soccer athletes using Raman spectroscopy to identify biomarkers of sports performance. Urine samples were collected from 20 athletes before and after exercise to be analyzed with a Raman microscope with excitation at 532 nm and a laser power of 67 mW. The analyses were compared with a group of 10 non-sports subjects. Raman analyses show peaks associated with the presence of urea, uric acid, creatinine, and ketone compounds with different intensity before and after exercise. The concentrations of urea, creatinine, and ketones were determined by commercial kits and were compared with the Raman analyses. The excretion of urea in urine increased after exercise in most volleyball athletes, while in some soccer players it decreased. The creatinine concentration increased significantly with exercise. The presence of ketones was observed in all of the spectra after exercise. The excretion of these metabolites is the result of the intensity and physical activity performed. Through this technique, we can evaluate athletes under training to establish their metabolic conditions and make nutritional adjustments to improve their athletic performance.